Evaluation of small‐group education on the shade determination ability of preclinical dental students—A controlled clinical trial. (17th April 2018) - Corcodel, N.; Krisam, J.; Klotz, A.‐L.; Deisenhofer, U. K.; Stober, T.; Hassel, A. J.; Rammelsberg, P.; Zenthöfer, A.
Abstract: Objectives: To evaluate the effect of small‐group education including practical training on dental students' shade determination performance compared with a control group. Methods: Sixty‐three non‐colour‐blind preclinical students were asked to participate and belonged to an intervention (n = 31) and a control (n = 32) group, respectively. All students received a lecture on dental shade determination. The members of the intervention group were educated and practically trained in small groups in addition. Ten volunteers, each with unrestored upper right middle and lateral incisors, were recruited. The students of both the intervention and control groups were then asked to determine the colour of the volunteers' test teeth using the 3D‐Master shade guide (Vita Zahnfabrik, Bad Säckingen, Germany) under artificial daylight illumination. For analytical purposes, the CIE L*a*b * coordinates were obtained using a spectrophotometer. Colour differences, Δ E, between all shade tabs selected by the students and the natural teeth were calculated. Δ E observed in the intervention and control groups were compared using t tests. In addition, a multi‐level regression model was adjusted for age and gender. Results: Mean (SD) Δ E between the shade tabs selected by the students and the natural teeth in the intervention and control groups were 3.8 (2.1) and 4.3 (2.3), respectively ( P < .001). The effect of group membership was reproduced in multivariate analysis whereas age and gender did not reach statistical significance. Conclusions: With more intensive education and practical training the ability to perform clinical shade determinations improved for students without previous clinical experience. The results obtained support the idea of implementing thematic small‐group education in the dental curriculum.